Semiotic Analysis of the movie ‘Yaavarum Nalam’ (2009) - Swamynathan, V (Journal of Advanced Research in Journalism & Mass Communication, 2023)
This study is a semiotic analysis of the 2009 movie “Yaavarum Nalam” using Saussure’s dyadic Theory. The ultimate aim of the horror genre is to bring the extreme emotion of deep fear inside the viewers. This research focuses on the Mise-en-scène the composition, lighting, costume, props, and any other object on frame can carry a meaning to the audience .The filmmaker’s structure their visualization with the layers of volatile metaphors in the mise - en - scene for the narrative. However deep the verbal information is, the visual representation of properties, acting, symbols, and the everything inside the frame plays a key role strengthens the narration. This research uses a qualitative method of analysis. The study is done analysing the signifier and the signified is interpreted using the elements of Mise – en – scene. The conclusions shows new camera angles introduced to represent the character’s feel in the situation, similar colors were used in both positive and negative aspects. How to cite this article: Swamynathan V. Semiotic Analysis on the Movie ‘Yaavarum Nalam’ (2009). J Adv Res Jrnl Mass Comm 2023; 10(1): 18-23. DOI: https://doi.org/10.24321/2395.3810.202304